Typing the settlements of Homokhátság - Szombathelyi, Sándor (Studia Mundi – Economica, 2021)
The status, problems and break out points of the Homokhátság have been examined by Bálint Csatári and his colleagues many times before. The uncategorized rural area in the classical interpretation is in big trouble because it should preserve its uniqueness and beauty despite the risk of desertification and the negative effects of the new age globalization. Studies and examinations are necessary so decision makers can get appropriate help and information to create effective action plans reinforced with financial plans which are Homokhátság specific and could achieve sustainable rural development based on the resources of the rural economy. The issues and methods of settlement categorisation are already known and have existed for a long time. This factor and cluster analysis executed in the SPSS application gives one answer to them. This article provides one possible solution to this problem.